Marriage Cancellation due to Force and Threats (Juridical Review of the Decision of the Religious Court of Tanjung Karang Regency Number 0174/Pdt.G/2020/PA.Tnk) - Kasmudin Harahap (LEGAL BRIEF, 2022)
Arrangements for the annulment of marriages are regulated in Articles 22 to 28 of the Marriage Law. In the provisions of Article 22 it is stipulates that "a marriage can be annulled if the parties do not meet the requirements to enter into a marriage." Article 25 of the Marriage Law stipulates that an annulment of a marriage can be made by submitting an application to the court in the legal area where the marriage is taking place or at the residence of both husband and wife. One of the reasons for the annulment of a marriage is that there is a threat that violates the law against the husband or wife (Article 27 Paragraph (1) of the Marriage Law), or in the implementation of the marriage there is coercion in Article 71 Letter f KHI. The basis for the judge's consideration in granting the Petitioner' s request was in the decision of the Tanjung Karang Religious Court Number 0174/Pdt. G/2020.PA. Tnk, that according to Law Number 50 of 2009 concerning Amendments to Law Number 7 of 1989 concerning the Religious Courts, the examination of cases of marriage annulments submitted by the Petitioners is the absolute and relative authority (competence) of the Tanjung Karang Religious Court. Furthermore, the arguments for the petitioner's petition are legally grounded, in accordance with the provisions of Article 27 Paragraph (1) of the Marriage Law in conjunction with Article 70 of the KHI.